Virtual reality cue exposure for the relapse prevention of tobacco consumption: a study protocol for a randomized controlled trial. Issue 1 (December 2016) - Giovancarli, Camille; Malbos, Eric; Baumstarck, Karine; Parola, Nathalie; Pélissier, Marie-Florence; Lançon, Christophe; Auquier, Pascal; Boyer, Laurent
Abstract Background Successful interventions have been developed for smoking cessation, but the success of smoking relapse prevention interventions has been limited. In particular, cognitive behavioural therapy (CBT) has been hampered by a high relapse rate. Because relapses can be due to the presence of conditions associated with tobacco consumption (such as drinking in bars with friends), virtual reality exposure therapy (VRET) can generate synthetic environments that represent risk situations for the patient in the context of relapse prevention. The primary objective of this study is to evaluate the effectiveness of CBT coupled with VRET, in comparison to CBT alone, in the prevention of smoking relapse. The secondary objectives are to assess the impact of CBT coupled with VRET on anxiety, depression, quality of life, self-esteem and addictive comorbidities (such as alcohol, cannabis, and gambling). A third objective examines the feasibility and acceptability of VR use considering elements such as presence, cybersickness and number of patients who complete the VRET program. Method/design The present study is a 14-month (2 months of therapy followed by 12 months of follow-up), prospective, comparative, randomized and open clinical trial, involving two parallel groups (CBT coupled with VRET versus CBT alone). The primary outcome is the proportion of individuals with tobacco abstinence at 6 months after the end of the therapy. Abstinence is defined by the total absence of tobacco consumption assessed during a post-test interview and with an apparatus that measures the carbon monoxide levels expired. A total of 60 individuals per group will be included. Discussion This study is the first to examine the efficacy of CBT coupled with VRET in the prevention of smoking relapse. Because VRET is simple to use and has a low cost, this interactive therapeutic method might be easily implemented in clinical practice if the study confirms its efficacy. Trial registration ClinicalTrials.gov Identifier:NCT02205060 (registered 25 July 2014).